IMPROVING SPEAKING SKILLS THROUGH COOPERATIVE LEARNING: A CASE STUDY - Erqulova Feruza Melikuziyevna; Habibillayeva Hilola Shavkatovna (Ustozlar uchun, 2025)
This article examines the effectiveness of cooperative learning in enhancing English speaking skills among 5th grade EFL students. Through a six-week case study at School No. 37, the research showed an 11% improvement in speaking performance following the use of strategies like Think-Pair-Share, group discussions, and role-play. The findings suggest that cooperative learning fosters a supportive environment that boosts confidence, fluency, and classroom participation.